R Dump Converter without DC Link Capacitor for an 8/6 SRM: Experimental Investigation - Pasumalaithevan Kavitha; Bhaskaran Umamaheswari (The Scientific World Journal)
The objective of this paper is to investigate the performance of 8/6 switched reluctance motor (SRM) when excited with sinusoidal voltage. The conventional R dump converter provides DC excitation with the help of capacitor. In this paper the converter used is the modified R dump converter without DC link capacitor providing AC or sinusoidal excitation. Torque ripple and speed ripple are investigated based on hysteresis current control. Constant and sinusoidal current references are considered for comparison in both DC and AC excitation. Extensive theoretical and experimental investigations are made to bring out the merits and demerits of AC versus DC excitation. It is shown that the constructionally simple SRM can be favorably controlled with simple R dump converter with direct AC excitation without need for DC link capacitor. A 4-phase 8/6 0.5 kW SRM is used for experimentation.